2006
DOI: 10.1590/s0100-879x2006000600015
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive changes in thyroid function of female rats fed a high-fat and low-protein diet during gestation and lactation

Abstract: The percent of lipids in the western diet has been continuously increasing in the last decades and is associated with a decrease in the proportion of protein intake. Recently, we demonstrated that protein malnutrition during lactation is associated with lower body weight and thyroid hypofunction in female rats and their offspring. Our objective in the present study was to determine if a high-fat and lowprotein diet was associated with similar changes. Three-month-old female Wistar rats were randomly assigned t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 39 publications
2
11
0
1
Order By: Relevance
“…A similar result was found by Brito et al, 9 who reported that dams fed a high-fat (24.2%) and low protein (7.0%) diet consumed less food during pregnancy, resulting in 82.0% less protein intake and 23.0% less energy intake, but fat intake was three times higher.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…A similar result was found by Brito et al, 9 who reported that dams fed a high-fat (24.2%) and low protein (7.0%) diet consumed less food during pregnancy, resulting in 82.0% less protein intake and 23.0% less energy intake, but fat intake was three times higher.…”
Section: Discussionsupporting
confidence: 87%
“…The significant decrease in food and energy intakes caused the POFG dams to lose a considerable amount of weight. Brito et al (2006) 9 also observed that dams fed a high-fat (24.2%), low-protein (7.0%) diet had lost 14.0% more weight by the end of the lactation period than the controls. During lactation, the negative weight gain coefficient per energy intake of the POFG is in agreement with their greater weight loss.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…Brito et al [24] reported that a high fat and low-protein diet could have a direct effect on TSH secretion or influence pituitary T 4 uptake or deiodination. In this study, all thyroid hormones, in parallel with leptin levels, significantly increased in the FD group as compared to the control group.…”
Section: Discussionmentioning
confidence: 99%